DEVELOPMENT OF TEACHING FACTORY IMPLEMENTATION MANAGEMENT MODEL TO INCREASE THE EFFECTIVENESS OF MARITIME-BASED BUSINESS MANAGEMENT - Hamjah; Albert Efendi Pohan; Hermansah (RADJA PUBLIKA, 2025)
This study is targeted to evaluate the linearity of teaching factory at SMKN 3 Kemaritiman Biak Numfor with aspects of context, input, process, and product. The respondents of this study consisted of teachers and students involved in the implementation of teaching factory. Data were collected through a questionnaire involving an assessment of a number of indicators relevant to the aspects being studied. The findings of the study indicate that teacher respondents consider teaching factory to be very linear with significant quality achievement values. Apart from these conditions, student respondents also consider teaching factory to be linear, although with slightly lower quality achievement values. The findings of this study also identified a number of aspects that still need attention, including the linearity of teaching factory implementation with the demands and conditions of society, supporting factors and production space facilities, implementation time arrangements, and Quality Control activities and increasing the linearity of teaching factory, it is recommended to strengthen understanding of the needs of industry and local labor markets, pay attention to supporting factors and production facilities, increase linear QC activities Standard Operating Procedure (SOP), and carry out innovation and close cooperation with industry and related stakeholders. This study provides significant benefits for SMKN 3 Kemaritiman Biak Numfor in improving the quality and linearity of teaching factory. The findings of this study are used as a foundation for developing more effective strategies and programs in preparing students for the world of work in industry.